DAMPAK PENERAPAN JARAK TANAM TERHADAP PRODUKTIVITAS DAN PENDAPATAN USAHATANI JAGUNG HIBRIDA DI LAHAN SAWAH TADAH HUJAN - Tota Suhendrata (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Corn (Zea Mays L) has multipurpose functions, as food, feed, industrial raw materials, and source offarmers' income. Rainfed rice fields are one of the potentials which have not been optimally utilized foragriculture, especially corn. Planting distance will affect productivity in two ways, 1) the use of plantingdistance that is too tight, plants will experience competition with other plants nearby and 2) plantingdistance that is too wide may reduce yield per unit area. This study aims to determine theperformance of productivity, income and feasibility and aslo to determine the break-even point ofproduction and prices. The study was conducted in Boloh Village, Toroh District, Grobogan Regencyon MT-3 in 2016 covering an area of ± 5 ha. The study was set out with 3 treatment distanceplanting, 75 x 20 cm (1 seed per hole), 75 x 40 cm (2 seeds per hole) and 50 x 50 cm (2 seeds perhole). The results showed that the 70 x 40 cm spacing treatment gave the highest productivity andincome. Hybrid maize farming with distance planting of 70 x 40 cm, both technically and financially, isthe most feasible to be developed in rainfed rice fields.